Anaïs, Henry, and June: Reading Nonmonogamy in Literature. Issue 3 (2nd July 2016) - Faucheux, Amandine
ABSTRACT: This article proposes a new reading methodology based on consensual nonmonogamous practices. Such a methodology, applied to texts whose characters engage in extramarital affairs, would shift the discussion from the axis of legitimacy/illegitimacy to an understanding of relationships based instead on mutual consent and sex positivity. Using Anaïs Nin's famous Journals (and particularly Volume I [1931-1934] and Henry and June: The Unexpurgated Diary (1931-1932) of Anaïs Nin ) as paradigm, the author argues that the story of Henry and June is that of a coming of age of a polyamorous woman. This bold claim allows the author to compare this understanding of Nin with that of scholars and literary critics who read her affairs as illegitimate (notably critics who immediately responded to the scandalous revelations of her affairs with the publication of Henry and June in 1986). Reading Nin as a polyamorist rather than an adulteress transforms our understanding of her actions and even her persona as a writer. As an adulteress, she is a self-deceiving liar, a selfish, hypersexual woman who broke her husband's heart, and whose writing can hardly be trusted to reveal the truth. As a polyamorist, we can separate her relationships entirely from questions of truth and morality by recognizing that multiple romantic and/or sexual relationships with different partners can be perfectly healthy and have no bearing on a person's moral character or skills. My proposition for a reading methodology based in polyamory calls for a reconsideration of the literary tradition of the adultery novel, and particularly its intrinsic misogyny and sex negativity. More generally, this article also urges literary scholars to pay attention to the impact of mononormativity (or the set of discourses that posit monogamy as natural and uniquely desirable) into cultural products such as novels as well as literary metatexts.